SKILLS OF INDEPENDENT LEARNING AND THE PRINCIPLES OF THEIR ORGANIZATION (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article explores the essential skills of independent learning and the principles underlying their effective organization. Independent learning skills, such as goal-setting, self-monitoring, critical thinking, time management, and reflective practice, are fundamental for students’ academic success and lifelong learning. The study examines methods for fostering these skills, including structured guidance, learner autonomy, and the integration of technological tools. Key principles for organizing independent learning activities are discussed, emphasizing clarity of objectives, scaffolding, feedback, and the creation of a motivating and supportive learning environment. The findings highlight the importance of combining theoretical knowledge with practical strategies to enhance learners’ self-regulation and promote active engagement in the learning process.